Online Single Submission and Legal Certainty for Foreign Investors in Indonesia - Rahmah, Najwa Aulia; Isnaeni, Fahriza Aulia; Angelita, Yolanda Syaftia (LIBERATICA, 2025)
The Online Single Submission (OSS) system was introduced by the Indonesian government as part of a regulatory reform aimed at simplifying business licensing, especially for foreign investors. This article critically examines two interrelated legal issues. First, it analyzes the normative framework governing OSS in the context of foreign investment, including its legal foundation under the Job Creation Law, Government Regulation No. 5 of 2021, and relevant ministerial regulations. The study explores the authority of OSS in issuing permits for foreign direct investment (FDI) and evaluates its position within Indonesia’s legal system. Second, the article assesses the extent to which OSS provides legal certainty for foreign investors under Indonesian positive law. This includes an analysis of transparency, procedural clarity, and regulatory consistency. Using a normative juridical method, the research identifies unresolved legal inconsistencies between OSS and sectoral or regional regulations. Findings suggest that while OSS strengthens administrative efficiency, its capacity to offer full legal certainty remains limited due to the fragmented regulatory environment and implementation gaps. The article concludes with recommendations for harmonizing legal instruments to enhance Indonesia’s investment climate.